(untitled) (Research, Society and Development, 2022)
The work proposed the correlation between electrical conductivity data and pH in treatments with different doses of copper. Copper plays central biochemical functions in the metabolism of living beings. However, it is considered a priority pollutant. As copper uptake is mediated by membrane H+-ATPases, and bioavailability is higher in acidic soils, toxicity can be detected in changes in pH and electrical conductivity. The work was modeled on onion bulbs, Allium cepa. Two treatments were established: 0.04 mg.L-1 Cu++ (treatment 1) and 0.40 mg.L-1 Cu++ (treatment 2), plus a control. Each treatment had six replications and were analyzed in four days of collection (1st, 7th, 8th and 16th days after planting - DAP). The plants were grown in distilled water until 7 DAP. On the 8th DAP, the solutions that defined the treatments: 0; 0.04 and 0.40 mg.L-1 Cu++ replaced the initial solution until collection at 16 DAP. There was morphological alteration in the roots submitted to the treatments. Inhibition of root growth was evident and there was no branching. There was a significant difference between doses when electrical conductivity (EC) and pH were analyzed. However, at the highest dose offered, 0.40 mg.L-1 Cu++ (treatment 2), EC did not change until 16 DAP. Plant growth in treatment 2 was compromised. Depending on the treatment, the plant may have tolerated lower doses, but could not resist the damage caused by toxicity at a tenfold higher level.